CONVALESCENT PLASMA THERAPY FOR COVID-19 PATIENTS: REGULATORY GUIDANCE ON COLLECTION, TESTING, PROCESSING, STORAGE, DISTRIBUTION, AND CLINICAL TRIALS - PORWAL, AMIT; PATHAK, KAMLA; PATHAK, DEVENDER; YADAV, RAMAKANT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Convalescent plasma can be transfused to patients suffering from the same infection or for preparing immunoglobulin concentrates. Plasma obtained from recovered patients can be a valuable alternative during the COVID-19 pandemic for supporting its treatment within a randomized or case-control clinical trials or observational studies of plasma transfusion and for preparing plasma-derived biological products. WHO Blood Regulators Network highlighted that a systematic approach for collecting convalescent plasma from patients recovered from COVID-19 could provide a useful intervention. Structured clinical trials can be used to assess safety and effectiveness of convalescent plasma. The convalescent plasma therapy is still in the experimental stage and is currently not included in the interim clinical guidelines of WHO. However, an emergency investigational new drug application (eIND) process has been induced to ensure the availability of COVID-19 convalescent plasma to the patients with severe or life-threatening COVID-19 conditions. USFDA is regularly amending its guidance as new results, and best practices are emerging. The write-up provides an overview of convalescent plasma, from a regulatory considerations viewpoint, systematic workflow protocol, and a cross-section of clinical trials underway.